Regional Disparities in Slovakia and The Czech Republic in the Context of Sustainable Growing of Energy Plants - Kotrla, Marián; Mandalová, Kristína; Prčík, Martin (European Journal of Sustainable Development, 2017)
The aim of the paper is to evaluate regional disparities in selected countries of Central Europe (Slovakia and the Czech Republic) in the context of sustainable growing of energy plants. Targeted growing of fast-growing energy plants can ensure increasing the share of renewable energy sources and contribute to the sustainable development of regions. Regional disparities in the possibility of biomass production of energy plants in Slovakia and the Czech Republic were evaluated according to soil and climatic factor. On average, 18.71% of the regions in Slovakia and 30.59% in the Czech Republic are less suitable for the agriculture use. These soils may be exempted from the agricultural land fund and used for non-food use. The real area of currently targeted growing of energy plants is low (0.0265% of the area of agricultural land fund in Slovakia and 0.0643% in the Czech Republic). Analysis of selected climate indicators confirms regional differences. The length of the vegetation period, as limiting factor of biomass production is more favorable in Slovak regions. Production ability of selected energy plants was monitored on model plantation in Nitra region (SK023). Biomass production of energy grass Miscanthus (27.95 t.ha-1) and energy plant Populus (after the second three-year yield cycle 135.14 t.ha-1) confirmed economically threshold yield after the six years of growing. Key words: sustainability; renewable energy; energy plants; regional disparities; Slovakia; The Czech Republic,